Harms of prolonged fasting in the preoperative period: Integrative review (Research, Society and Development, 2024)
The objective was to identify the harms of prolonged fasting in the preoperative period. Methods: This is an integrative literature review, in which the PICO strategy was used to search for scientific articles. Results: Most studies showed that patients remained fasting for a much longer time than recommended in the literature, in addition there was no distinction between fasting hours and liquid and solid foods. Other studies pointed to the benefits of shortening preoperative fasting. Some articles highlighted the benefits of using clear carbohydrate solutions a few hours before surgery. There were also studies that evaluated nurses' perception of the preoperative fasting period. Conclusion: The present study demonstrated the importance of avoiding prolonged fasting, avoiding its harm. Abbreviating fasting, in addition to reducing the damage caused by postoperative metabolic changes, reduces patients' hospitalization and recovery time.